Pengamatan hasil olahan daun beluntas (Pluchea indica L.) terhadap sifat fisika dan kimianya - Idiek Donowarti; Fidhiani Dayang Diah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
This study was carried out to determine some bioactive phytochemicals in beluntas commonly consumed in Java, Indonesia. It is also to know the effect of fruit processing forward its phytochemicals content. This research comprised two steps including qualitative and quantitative test. The result of qualitative test showed that Pluchea indica L containing of alkaloid and polyphenols. Based on its polyphenols content, Pluchea indica L boiled was the best treatment. The light green variety has total polyphenol value 83,113 mg/g with the brightness (L*) and the greeness (a) value are 46,400 and 2,967. Furthermore, the fresh pluchea indica leaf has total polyphenol value 39,135mg/g with the brightness (L*) and the greeness (a) value are 46,067 and 2, respectively. Fruit processing intervariety of Pluchea indica L did not give significant effect on water content. Besides, variety and fruit processing did not give significant effect on colour (b). The solute n-hexane to analize with thin layer chromatography indicated that this bolied pluchea iindica leaf content terpenoid compound. Bioactive phytochemicals are widely distributed in these foods, although their concentrations are variable among the different types of fruits. These results indicate that this fruits may provide a potential source of dietary antioxidant as a functional food.